Comparisons of PI and ANN controllers for shunt HPF based on STF-PQ Algorithm under distorted grid voltage - Mohamed Asghaiyer Omran; Izzeldin. I. Ibrahim; Abu Zaharin Ahmad; Mohamed Salem; Mohamad Milood Almelian; Awang Jusoh; Tole Sutikno (Institute of Advanced Engineering and Science, 2019)
This paper proposes a shunt hybrid power filter (HPF) for harmonic currents and reactive power compensation under a distorted voltage and in a polluted environment. For this purpose, the reference current of the shunt HPF is computed based on the instantaneous reactive power (p-q) theory with self-tuning filter (STF). In order to adjust the dc voltage as a reference value, PI and ANN controllers have been utilized. Moreover, the system has been implemented and simulated in a MATLAB-SIMULINK platform, and selected results are presented. Therefore, the results verified the good dynamic performance, transient stability and strong robustness of the ANN controller. Furthermore, the shunt HAPF with ANN controller has been found to be in agreement with the IEEE 519-1992 standard recommendations on harmonic levels.